Toxic Shock Syndrome Toxin-1 (TSST-1) in Staphylococcus aureus: Prevalence, Molecular Mechanisms, and Public Health Implications - Rahima Touaitia; Nasir Adam Ibrahim; Eman Abdullah Almuqri; Nosiba S. Basher; Takfarinas Idres; Abdelaziz Touati (Toxins, 2025)
Staphylococcus aureus is a significant pathogen responsible for various infections, with its production of toxic shock syndrome toxin-1 (TSST-1) being a central factor in the pathogenesis of toxic shock syndrome (TSS). This study investigates the prevalence, molecular mechanisms, and public health implications of TSST-1-producing S. aureus. This study reviews methods for detecting TSST-1, focusing on PCR-based molecular techniques and immunological methods like ELISA, as well as the challenges in accurately diagnosing TSST-1 due to antibiotic resistance and strain variability. The findings reveal that TSST-1 is widely distributed across clinical, foodborne, and zoonotic sources, with significant prevalence in both healthcare and agricultural settings. This study also discusses the regulatory networks controlling TSST-1 production, including the agr system and other environmental cues like glucose, iron, and pH levels, which influence toxin expression. The results underline the need for improved surveillance and diagnostic approaches, as well as the development of targeted therapies to mitigate the impact of TSST-1 in both hospital and community settings. The conclusions highlight the importance of understanding TSST-1’s molecular mechanisms for developing effective public health strategies to control its spread.